The Habit of Dhuha Prayer in Forming Children Character - Nikmatur Rodiyah; Mispani Mispani; Amirudin Amirudin (International Journal on Advanced Science, Education, and Religion, 2024)
The aim of this research is to find out the relationship between Duha prayers and the formation of children's character, as well as to see how to carry out Duha prayers and see children's ability to memorize through Duha prayer habituation activities. This habituation method is based on experience, because what gets used to is something that is practiced. This type of research is a type of qualitative field research, namely research based on field data related to the research topic. Qualitative research method, the type used in this research is descriptive qualitative. Data collection techniques use observation, interviews, documentation. Every day, before the teaching and learning process begins, dhuha prayers are performed at the Abu Bakar Mosque belonging to the Ainul Falah Islamic Boarding School. The cottage is next to the madrasa and closer to MI Ma'arif NU 5 Sumbergede than to the mosque belonging to the madrasa foundation. in the morning, precisely at 07.00 WIB until finished. Implementation of Dhuha prayers in congregation to optimize the quality and quantity of religious aspects as well as the practice of speaking loudly. The results of this research shows that according to the spiritual intelligence of class IV students of Mi Ma''arif Nu 5 Sumbergede, with the dhuha prayer routine they form individuals who are Istiqomah, which means they are always active and enthusiastic. Trustworthy, which means they always carry out tasks at home happily. Honest means they don't lie to their parents. Discipline means they are always on time, have the habit of obeying rules and regulations. Responsibility means carrying out one's duties and obligations. Patience means being able to wait your turn and queue in an orderly manner. Tolerance means respecting differences of opinion. Keywords: Habituation Duha Prayer, Education Character